Economic Gains for U.S. States from Educational Reform - Eric A. Hanushek; Jens Ruhose; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2015)
There is limited existing evidence justifying the economic case for state education policy. Using newly-developed measures of the human capital of each state that allow for internal migration and foreign immigration, we estimate growth regressions that incorporate worker skills. We find that educational achievement strongly predicts economic growth across U.S. states over the past four decades. Based on projections from our growth models, we show the enormous scope for state economic development through improving the quality of schools. While we consider the impact for each state of a range of educational reforms, an improvement that moves each state to the best-performing state would in the aggregate yield a present value of long-run economic gains of over four times current GDP.
Keywords: I21; J24; O47; 330; economic growth; human capital; cognitive skills; schooling; U.S. states